Mapping of Co-curricular Achievements in Kurikulum Merdeka with the Problem-Centered Thinking Skills Model - Tuti Utami; Rudi Susilana; Laksmi Dewi (STAI Hubbulwathan Duri, 2024)
This study aims to illustrate the mapping of co-curricular achievements in Kurikulum Merdeka as an effort to build adaptive co-curricular programs utilizing the Problem-Centered Thinking Skills (PCTS) model. By analyzing the relevant documents and regulations, including the implementation guidelines of Kurikulum Merdeka, the dimensions, elements, and sub-elements of the co-curricular programs are analyzed. The findings indicate that a significant portion of co-curricular achievements can be effectively developed into adaptive programs through the application of the PCTS model. This study highlights the importance of integrating the PCTS model in shaping adaptive co-curricular activities that promote critical thinking skills and enhance students' critical thinking within the framework of Kurikulum Merdeka. These insights provide practical recommendations for educators, curriculum designers, and policymakers to facilitate the formation of adaptive co-curricular programs that foster student engagement and develop essential skills. By incorporating the PCTS model, co-curricular activities can become dynamic platforms for students to actively participate in real-world problem-solving, nurturing their critical thinking abilities.